Offshore Experimental Work of a Pump Directly Driven by a Fully Passive Dual-Flapping-Foil Hydrokinetic Turbine - Jihoon Kim; Sejin Jung; Muhea Jung; Sangkyu Choi; Dasom Jeong; Jin Hwan Ko (Journal of Marine Science and Engineering)
In this study, a previously developed fully passive hydrokinetic turbine with two flapping foils was used to directly drive a reciprocating pump, and the performance of this system was investigated at an offshore site in Republic of Korea. The fully passive operation of the turbine worked effectively due to its coupling mechanism, and pumping was successfully carried out during flood tides when the pumping height was consistently maintained using a water level gauge and winch system. Pumping occurred at a height of approximately 9 m when the flow velocity reached 1.8 m/s, at which point the corresponding Reynolds number exceeded one million. In one case where a high pumping flow rate was achieved during offshore trials conducted over a period of time, the pumping efficiency reached up to 34% when the reduced frequency of the turbine was 0.126, falling within the known optimum range. The pump driven by the flapping-foil hydrokinetic turbine, which can be positioned near the shore or in shallow water, could provide a viable solution for off-grid communities needing to pump seawater or generate hydroelectric power.